Ethyl 6-methylsulfanyl-2-phenyl-1H-imidazo[1,2-b]pyrazole-7-carboxylate monohydrate - Shao, Teng-fei (International Union of Crystallography, 2009)
The title compound, C(15)H(15)N(3)O(2)S·H(2)O, has been obtained in a search for new imidazo[1,2-b]pyrazole derivatives with better biological activity. The 1H-imidazo[1,2-b]pyrazole plane forms a dihedral angle of 16.90 (3)° with the benzene ring. π–π interactions are indicated by the short distance of 3.643 (2) Å between the centroids of the benzene and imidazole rings. The crystal structure also involves intermolecular O—H⋯N hydrogen bonds.